Pengaruh Lama Penyimpanan Benih Padi Merah (Oryza nivara L) Varietas Pamelen Dan Dosis Pupuk Npk Terhadap Pertumbuhan Dan Hasil - Suci Renikasari; Yekti Maryani; Djoko Heru Pamungkas (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the effect of storage time of red rice (Oryza nivara L.) pamelen variety and the dose of NPK Phonska fertilizer on growth and yield.This research was carried out in a self-help agricultural and rural research center (P4S) “Lestari Makmur”.Located on jalan Wates km 12,Semampir Hamlet,Argorejo village,Sedayu District regency,Yogyakarta. The agro-climatic nature of the research area is a low area with an altitude of 88 meters above sea level,the type of soil is regosol with a pH of 5,5-7 with an average temperature of 26-32 and a rainfall of 1.654 mm/year.Held in november 2021-march 2022.The experimental design used in this study was a 3x3 factorial design using a completely randomized block design (RAKL) and using a tile planting system with two treatment factors.The first factor is (A1) the duration of storage of rice seeds for 1 month, (A2) the duration of storage of rice seeds for 2 months, (A3) storage time of rice seeds for 3 months. The second factor is the application of NPK and Phonska fertilizer at a dose B1 (300) kg/ha,B2 (400) kg/ha and B3 (500) kg/ha. Obsevation variables included plant height, number of tillers,number of panicles, fresh weight of stover, dry weight of stover, percentage of empty seeds, percentage of pithy seeds,weight of 1000 grains,moisture content and weight of grain per hectare.Analysis of observations using variance at 5% level followed by the Duncan's Multiple Range Test (DMRT) distance test at a level of = 5%. Research result can be concluded that There was no interaction between the length of storage of rice seeds and the dosage of Phonska NPK fertilizer on the growth and yield variables of pamelen red rice plants. The treatment of long storage of rice seeds showed no significant difference to the growth and yield of pamelen red rice varieties. Phonska NPK fertilizer dose treatment showed no significant difference on the growth and yield of pamelen variety red rice plants.